An experimental study on near-field tip vortex of an elliptical hydrofoil using tomographic particle image velocimetry - Zhao, Hang; Tu, Han; She, Wenxuan; Gao, Qi; Cao, Yantao; Peng, Xiaoxing; Shao, Xueming (Experiments in fluids, 2023)
Volumetric measurement for the non-cavitating tip vortex in the near field of an elliptical hydrofoil is conducted using tomographic particle image velocimetry, which provides a fully three-dimensional diagnose of the vortex formation and development. The wandering motion and flow properties of the near-field tip vortex under different incident angles and Reynolds numbers are investigated in detail. Unlike in the far field, the wandering motion in the near field is mainly subject to the local flow unsteadiness rather than the flow condition. By the “re-centered” post-processing, the deviations introduced by the wandering motion can be technically corrected, and more accurate vortex properties can be thus obtained. In the near field, a turning point of the vortex center trajectory is detected, the position of which is basically independent of the flow condition. By investigating the local flow properties, it is found that this turning point is the position where the tip vortex completely leaves the trailing edge of hydrofoil and enters the wake region. At this turning point, the external supply to the vortex core starts to be restricted, and the vortex circulation reaches a rather constant value. Further according to the local flow properties, the development process of the near-field tip vortex can be divided into three stages: vortex-attached stage, vortex-lifting stage and vortex-detached stage, which are found to be closely relevant to the hydrofoil configuration.